IMPROVING XI-GRADE STUDENTS’ WRITING ESSAY SKILL USING COMPUTER EDUTAINMENT - Yulandari, Evi Safitri; Rahman, Arif (JOLLT Journal of Languages and Language Teaching, 2019)
As viewed by many linguists, writing skill is the most difficult one in English to be tough or learned. For many years, writing has not been a favorable interest like the other skills. This paper is intended to discuss the role and the effectiveness of using computer edutainment or called Education and Entertainment in improving studentsâ€™ writing. The subjects of this research were the studentsâ€™ class XI A. Meanwhile, the objects of this research are studentsâ€™ skill in writing through Computer Edutainment. In this research the researcher used CAR (Classroom Action Research) as the research method, there is 2 technique of collecting the data in this research those are qualitative data and quantitative data. The quantitative data are in the form of numerical data. The data are from students’ score of pre-test and post-test while the qualitative used in collecting the data were taken from the result of observation and interview. This study used several data instrument in gathering the data dealing with the question of the study, i.e: writing test in the form of writing essay, observation field note, and interview. The data were then analyzed whether their writing results were reaching the minimum standard or not, and having improvement or not. From the comparisons, the researcher makes a conclusion in the form of descriptions whether the students’ ability of XI of SMAN 1 PAJO in writing has improved by the use of computer edutainment or not.